SEBARAN STOK KARBON VEGETASI MANGROVE DI WILAYAH PESISIR KECAMATAN LAINEA KABUPATEN KONAWE SELATAN MELALUI ANALISIS BACKSCATTER CITRA SATELIT RADAR ALOS PALSAR L-BAND - Zulkarnain Zulkarnain; Sitti Marwah; Lia Sartika (Jurnal Ecogreen, 2016)
This study has been carried out to know  the carbon stock distribution of Mangrove, to validate ALOS PALSAR backscattering coefficient with aboveground biomass (AGB)  and to know the best polarization to estimate mangrove  carbon stock distribution  at Coastal zone of Lainea District of South Konawe. This study was conducted from December 2015 to June 2016 at coastal zone of Lainea sub district of  South Konawe. Above ground biomass was estimate by allometric equation and ALOS PALSAR Dual Polarization HH-HV analysis. The relationship between  two variables then analyzed mathematically by regression to see how strong the relationship between two variables. The criteria used by coefficient of determination R2 and Root Mean Square Error (RMSE). The result of total carbon stock in sample plot  is 71,97 ton ha-1 with  total biomass  is 153.13 ton ha-1. For determination, coefficient HV is higher than HH with coefficient of determination R2  is 84% and for RMSE value HV is lower than HH with 1,38 than 2,01. So, for mapping carbon stock distribution worth using HV backscatter polarization. Map of carbon stocks distribution classified by three class distribution are 0-25 ton ha-1 for low carbon stock marked by blue color, 26-50 ton ha-1 for medium carbon marked by yellow color and 51-75 ton ha-1 for high carbon marked by red color.  Based on the value of R2 and RMSE, we conclude that the utilizing of ALOS PALSAR HV with equation y= 0.254HV - 18.93  polarization satellite imagery worthy used for estimating and mapping of carbon stock distribution of mangrove forest in Lainea Sub District, South Konawe Keywords : ALOS PALSAR, Mangrove Forests, Carbon Stock, Validation